Comprehensive evaluation of hydro-liquefaction characteristics of lignocellulosic subcomponents. Issue 4 (August 2020) - Li, Qingyin; Hu, Xun; Liu, Dong; Song, Linhua; Yan, Zifeng; Li, Ming; Liu, Qing
Abstract: This study investigated the hydro-liquefaction behaviors of cellulose, xylan and lignin in ethanol at various temperatures. The interactions between the reaction medium and individual biomass component under different temperatures were evaluated using the Monte Carlo method. The simulation results indicated that the compatibility from cellulose and xylan system was superior to that of lignin with the elevated temperature. The liquefaction characteristics of cellulose and xylan were highly affected by temperature variation due to the existence of active chemical region and functional groups in the structures. In comparison, the reaction behavior of lignin-containing complicated polyaromatic structure was slightly dependent on the elevated temperature. The variation trend of chemical structures from solid residues was highly related to the nature of the raw feedstock. The properties of bio-oil derived from liquefaction of single biomass composition were also associated with the inherent composition of each biomass subcomponent. Graphical abstract: Image 1 Highlights: Monte Carlo method was utilized to study the liquefaction behavior of subcomponents. The behavior of subcomponents was associated with the inherent chemical structure. The composition of bio-oil highly depended on the type of raw feedstock.